Approximate Single-Diode Photovoltaic Model for Efficient I-V Characteristics Estimation. (5th November 2013) - Ma, Jieming; Man, Ka Lok; Ting, T. O.; Zhang, Nan; Guan, Sheng-Uei; Wong, Prudence W. H.
Abstract : Precise photovoltaic (PV) behavior models are normally described by nonlinear analytical equations. To solve such equations, it is necessary to use iterative procedures. Aiming to make the computation easier, this paper proposes an approximate single-diode PV model that enables high-speed predictions for the electrical characteristics of commercial PV modules. Based on the experimental data, statistical analysis is conducted to validate the approximate model. Simulation results show that the calculated current-voltage ( I - V ) characteristics fit the measured data with high accuracy. Furthermore, compared with the existing modeling methods, the proposed model reduces the simulation time by approximately 30% in this work.